Kesulitan Guru Kelas Dalam Mengembangkan Modul Ajar Di SD Yayasan Pendidikan Nurcahaya Medan - Aufa Aufa; Nurul Aflah (Institut Agama Islam Hidayatullah Batam, 2025)
The objective of this study is to examine the challenges faced by classroom teachers in developing and implementing teaching modules. The method employed in this research is descriptive qualitative. Data collection was conducted through interviews, observations, and documentation. Data analysis utilized three main stages: data reduction, data display, and conclusion drawing. Based on the findings, the challenges teachers face in developing teaching modules include a lack of understanding in interpreting Learning Outcomes (CP), inability to formulate Learning Objectives (TP) based on existing CP, and difficulties in constructing the Learning Objective Flow (ATP) from TP. In the implementation stage, teachers often encounter obstacles in determining the selection of media, learning models, and assessments that are appropriate, thus failing to align with the diverse individual characteristics of students according to their developmental stages.characteristics of different students according to their developmental phases